If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 5 = -14 Reorder the terms: 5 + 6x = -14 Solving 5 + 6x = -14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 6x = -14 + -5 Combine like terms: 5 + -5 = 0 0 + 6x = -14 + -5 6x = -14 + -5 Combine like terms: -14 + -5 = -19 6x = -19 Divide each side by '6'. x = -3.166666667 Simplifying x = -3.166666667
| 5x^2+7x=1 | | -755=23(x+30)+5(1+7x) | | 7(3x+4)=15x+8 | | 2.3c-12=13 | | -30(28k-79)+34(1-16k)=-364 | | 35+40=20x | | 5(4x-4)=45 | | (32x^10)-1/5 | | (X-3)(x+4)=80 | | 35+40=20 | | 5tanx-5=0 | | ax-2x=a^2-4 | | (x+2)(x+3)(x+4)(x+1)=24 | | 64x=0 | | 4a=3a-7 | | 28y-(5x-17y)= | | 11x-24-5x= | | 11x-24-5x=16x-24 | | 2x+86=50 | | 6x-5=-15(x+5) | | 28+8x=8x+27+2 | | -6(2t+9)=-42 | | 6p-4p=3p-4 | | A/25 | | 2x=6+26 | | 3y-5*4=2y+1 | | 4y+16x=-28 | | 5(f-3)=20 | | (X-3)/4=1/2 | | (9*x)+(5*y)=28 | | 3.4+0.2d=1.4 | | 2mx+(m-2)y-2=0 |